Electrical conduction in plasma polymerized thin films of γ‐terpinene. Issue 30 (2nd May 2015) - Ahmad, Jakaria; Bazaka, Kateryna; Vasilev, Krasimir; Jacob, Mohan V.
ABSTRACT Plasma polymerized γ‐terpinene (pp−GT) thin films are fabricated using RF plasma polymerization. MIM structures are fabricated and using the capacitive structures dielectric properties of the material is studied. The dielectric constant values are found to be in good agreement with those determined from ellipsometric data. At a frequency of 100 kHz, the dielectric constant varies with RF deposition power, from 3.69 (10 W) to 3.24 (75 W). The current density–voltage (J−V) characteristics of pp–GT thin films are investigated as a function of RF deposition power at room temperature to determine the resistivity and DC conduction mechanism of the films. At higher applied voltage region, Schottky conduction is the dominant DC conduction mechanism. The capacitance and the loss tangent are found to be frequency dependent. The conductivity of the pp−GT thin films is found to decrease from 1.39 × 10−12 S/cm (10 W) to 1.02 × 10−13 S/cm (75 W) and attributed to the change in the chemical composition and structure of the polymer. The breakdown field for pp–GT thin films increases from 1.48 MV/cm (10 W) to 2 MV/cm (75 W). A single broad relaxation peak is observed indicating the contribution of multiple relaxations to the dielectric response for temperature dependent J−V. The distribution of these relaxation times is determined through regularization methods. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42318.